Systematic Review of Polyherbal Combinations Used in Metabolic Syndrome - Palla, Amber Hanif; Amin, Faridah; Fatima, Bilqees; Shafiq, Arooj; Rehman, Najeeb Ur; Haq, Ikram ul; Gilani, Anwar-ul-Hassan (Frontiers in Pharmacology, 2021)
Background: Metabolic syndrome (MetS) is a multifactorial disease, whose main stay of prevention and management is life-style modification which is difficult to attain. Combination of herbs have proven more efficacious in multi-targeted diseases, as compared to individual herbs owing to the “effect enhancing and side-effect neutralizing” properties of herbs, which forms the basis of poly-herbal therapies This led us to review literature on the efficacy of herbal combinations in MetS. METHODS: Electronic search of literature was conducted by using Cinnahl, Pubmed central, Cochrane and Web of Science, whereas, Google scholar was used as secondary search tool. The key words used were “metabolic syndrome, herbal/poly herbal”, metabolic syndrome, clinical trial” and the timings were limited between 2005-2020. RESULTS: After filtering and removing duplications by using PRISMA guidelines, search results were limited to 41 studies, out of which 24 studies were evaluated for combinations used in animal models and 15 in clinical trials related to metabolic syndrome. SPICE and SPIDER models were used to assess the clinical trials, whereas, a checklist and a qualitative and a semi-quantitative questionnaire was formulated to report the findings for animal based studies. Taxonomic classification of Poly herbal combinations used in animal and clinical studies was designed. CONCLUSION: With this study we have identified the potential polyherbal combinations along with a proposed method to validate animal studies through systematic qualitative and quantitative review. This will help researchers to study various herbal combinations in MetS, in the drug development process and will give a future direction to research on prevention and management of MetS through poly-herbal combinations.